Prmt1-mediated histone H4R3me2a methylation regulates the proliferation, migration and invasion of laryngeal cancer cells by affecting the expression level of NCOA5 - Li, Linlu; Cui, Jiao; Li, Xiaoyu; Zhu, Yuting; Wu, Hongfei; Zhou, Lanzhu (Frontiers in Oncology, 2024)
BackgroundLaryngeal cancer is a common head and neck cancer, and its occurrence and development are closely related to a variety of epigenetic modifications. protein arginine methyltransferase 1 (PRMT1) is an important type I protein arginine methyltransferase, which catalyzes the monomethylation and asymmetric dimethylation of arginine and participates in the occurrence and development of a variety of cancers. Current research has found that the expression of PRMT1 is increased in laryngeal carcinoma tissues. Histone modifications play a key role in regulating gene expression and maintaining cellular function. In particular, histone H4 arginine 3 dimethylation (H4R3me2a) has been shown to be associated with the development of a variety of cancers. Nuclear Receptor Coactivator 5 (NCOA5) is an important nuclear receptor coactivator, which regulates gene expression through the interaction between various nuclear receptors and other transcription factors. The present study aimed to investigate how PRMT1-mediated H4R3me2a methylation affects the proliferation, migration and invasion of laryngeal cancer cells and to verify the role of NCOA5 in this process.MethodsThe expression of PRMT1 and NCOA5 was inhibited by siRNA mediated gene knockdown in laryngeal cancer cells. The changes of H4R3me2a protein levels were detected by Western Blotting, and cell proliferation, migration and invasion abilities were evaluated by CCK-8, cell scratch assay, Transwell migration and invasion assay. RT-qPCR was used to detect the mRNA expression levels of related genes. The overexpression experiment of NCOA5 was carried out by constructing overexpression vector to verify its effect.ResultsAfter PRMT1 knockdown, the expression of H4R3me2a in laryngeal cancer cells was significantly decreased, and the cell proliferation, migration and invasion abilities were weakened. Similarly, knockdown of NCOA5 expression also resulted in decreased H4R3me2a levels and attenuated cell proliferation, migration and invasion. Overexpression of NCOA5 partially restored H4R3me2a levels and cell proliferation, migration and invasion abilities.